Unraveling the Digital Drivers of Customer Satisfaction: Digital Marketing, E-Channel Experience, and Brand Image at PT Bank Mandiri - Sunarjo, Wenti Ayu; Putra, Gilang Kharisma; Handayani, Tri; Mulyapradana, Aria (LPPM Universitas Pekalongan, 2025)
The digital era is driving a shift in consumer behaviour, where customers increasingly demand fast, easy, transparent, and accessible services without having to come to a branch office. The purpose of this study is to analyse the influence of digital marketing, e-channels, and brand image on customer satisfaction at PT. Bank Mandiri Tbk, especially among millennials and Gen Z in Pekalongan City. This study applies a quantitative approach using a survey method as the main data collection technique. The sample consisted of 110 respondents who were customers of PT. Bank Mandiri Tbk, aged 17-35 years, and domiciled in Pekalongan City. The data collection instrument was a questionnaire with a Likert measurement scale. Data analysis was carried out through several stages, including validity testing, reliability testing, and classical assumption testing, as well as simple linear regression and t-tests, all of which were processed using SPSS software. Based on the results of data processing, it was found that the variables of digital marketing, e-channels, and brand image contributed positively and significantly to customer satisfaction. Keywords: Digital Marketing, E-Channel, Brand Image, Customer Satisfaction